Intrauterine balloon tamponade for management of severe postpartum haemorrhage in a perinatal network: a prospective cohort study. (25th October 2016) - Revert, M; Cottenet, J; Raynal, P; Cibot, E; Quantin, C; Rozenberg, P
Abstract : Objective: To evaluate the effectiveness of intrauterine balloon tamponade (IUBT) for management of severe postpartum haemorrhage (PPH). To identify the factors predicting IUBT failure. Design: Prospective cohort study. Setting: Ten maternity units in a perinatal network. Population: Women treated by IUBT from July 2010 to March 2013. Methods: The global IUBT success rate was expressed as the number of women with severe PPH who were successfully treated by IUBT divided by the total number treated by IUBT. IUBT failure was defined as the need for arterial embolisation or surgery. Logistic regression analysis was used to estimate factors predicting IUBT failure. Main outcome measures: Global IUBT success rate. Factors associated with IUBT failure. Results: Intrauterine balloon tamponade was attempted in 226 women: 171 after vaginal delivery (VD) (75.7%) and 55 during or after caesarean delivery (CD) (24.3%). The global success rate was 83.2% (188/226) and was significantly higher after VD (152/171, 88.9%) than CD (36/55, 65.5%, P < 0.01). The percentage of CD was significantly higher in the failure group (50.0 versus 19.1%, P < 0.01), as was mean (SD) estimated blood loss before IUBT: 1508 ± 675 ml versus 1064 ± 476, P < 0.01. Coagulopathy was significantly more frequent in the failure group (50.0% versus 17.2%, P < 0.01). CD [Odds ratio (OR) 3.5; 95% CI 1.6–7.6], estimated blood loss before IUBT (OR 3.2; 95% CI 1.5–6.8) and coagulopathy (OR 5.6; 95% CI 2.5–13.0) were predictive of IUBT failure. Conclusion: Intrauterine balloon tamponade is an effective method for treating severe PPH. Early balloon deployment before the development of coagulopathy increases its success rate. Tweetable abstract: Intrauterine balloon tamponade is effective for achieving haemostasis in intractable postpartum haemorrhages. Tweetable abstract: Intrauterine balloon tamponade is effective for achieving haemostasis in intractable postpartum haemorrhages.